Molecular dynamics simulations of the isolated domain 1 of annexin I - Huynh, Tru; Smith, Jeremy C. (Theoretical chemistry accounts, 1998)
Annexin molecules consist of a symmetrical arrangement of four domains of identical folds but very different sequences. Nuclear magnetic resonance (NMR) experiments on the isolated domains of annexin I in aqueous solution have indicated that domain 1 retains its native structure whereas domain 2 unfolds. Therefore these two domains constitute interesting models for comparative simulations of structural stability using molecular dynamics. Here we present the preliminary results of molecular dynamics simulations of the isolated domain 1 in explicit water at 300 K, using two different simulation protocols. For the first, domain 1 was embedded in a 46 Å cubic box of water. A group-based non-bonded cut-off of 9 Å with a 5-9 Å non-bonded switching function was used and a 2 fs integration step. Bonds containing hydrogens were constrained with the SHAKE algorithm. These conditions led to unfolding of the domain within 400 ps at 300 K. In the second protocol, the domain was embedded in a 62 Å cubic box of water. An atom-based non-bonded cut-off of 8-12 Å using a force switching function for electrostatics and a shifting function for van der Waals interactions were used with a 1 fs integration step. This second protocol led to a native-like conformation of the domain in accord with the NMR data which was stable over the whole trajectory (∼2 ns). A small, but well-defined relaxation of the structure, from that observed for the same domain in the entire protein, was observed. This structural relaxation is described and methodological aspects are discussed.